Acoustic issues of sacral structures - NIEMAS, M.; SADOWSKI, J.; ENGEL, Z. (Archives of Acoustics, 1998)
In the paper sacral structures treated as speech-music halls were evaluated in terms of acoustic properties. The basic acoustic issues occurring at a planning stage as well as the methods of evaluation of the finished, existing and being modernized interior acoustic quality of sacral structures are discussed. Acoustic requirements refer to some type of liturgical ceremonies, and to cultural activities performed as well in those structures. The current status of church acoustics in structures built in different periods up to 1950 is presented. The methods of evaluation of the sacral interiors acoustic quality are nowadays significantly improved. They are discussed on an example of newly designed churches.